Attitude of Consumers Towards Community Pharmacists and Their Interest in Expanding Community Pharmacist Services in Basra, Iraq: A pilot study - Adheed Khalid Sharrad (College of Pharmacy / Mustansiriyah University, 2018)
The public only views a few pharmacists as the foremost health care professionals who are responsible for the utilisation of medicines to prevent or treat disease. The study aims to explore the attitude of patients towards the practice and roles of community pharmacists and to evaluate the services offered by community pharmacists working in Basra city. A total of 150 cross sectional surveys were given to patients who were visiting the community pharmacies. SPSS version 17 was used to conduct the descriptive analysis. There was a 71.3% response rate, and 71% were males. 58% of the participants believed that the pharmacists were businessmen. Furthermore, 64.49% stated they first communicate with the physician to obtain answers to a drug-related problem or question. A majority of the respondents (66%) stated that they consulted their pharmacist in the case of minor health problems. Positive view regarding the expanded role of the community pharmacists.Thus, to improve the practice of community pharmacy and to implement pharmaceutical care successfully in community pharmacies in Iraq, efforts should be concentrated towards addressing and identifying issues and promoting the roles that community pharmacists have in monitoring drug therapy and in working as a public drug information resource